Pengaruh Citra Merek, Kemasan dan promosi terhadap keputusan pembelian produk Big Cola di Kota Batam - JACKLYN BERNITA ADE ENG ENG; Tiurniari Purba (LPPM Universitas Putera Batam, 2025)
This study aims to determine the influence of brand image, packaging, and promotion variables on purchasing decisions for Big Cola products in Batam City. The sampling technique used snowball sampling because the number of samples was unknown, so the number of respondents in this study was 100 respondents. Data were processed using SPSS (Statistical Product and Service Solution) version 26. The analysis methods used were descriptive statistical tests, validity tests, reliability tests, classical assumption tests, influence tests, and hypothesis tests. From the results of the study, it shows that brand image, packaging, and promotion have a significant influence simultaneously on Big Cola product decisions in Batam City. The results of the determination coefficient analysis state that brand image, packaging, and promotion have a significant influence on Big Cola product purchasing decisions by 74.8%. While the rest is influenced by other variables not studied.